ATR-FTIR spectroscopic methods for analysis of black seed oil from alginate beads - Alkhatib, Hamzeh; Mohamed, Farahidah; Doolaanea, Abd Almonem (Innovare Academics Sciences Pvt. Ltd, 2018)
Objective: This study aimed to use attenuated total reflectance-fourier transform infrared spectroscopy (ATR-FTIR) for rapid quantification of black seed oil (BSO) from alginate beads and to develop simple analysis method for in vitro release study based on turbidity measurement.